Profile of Histone H3 Lysine 4 Trimethylation and the Effect of Lipopolysaccharide/Immune Complex-Activated Macrophages on Endotoxemia - Ruenjaiman, Vichaya; Butta, Patcharavadee; Leu, Yu-Wei; Pongpanich, Monnat; Leelahavanichkul, Asada; Kueanjinda, Patipark; Palaga, Tanapat (Frontiers in Immunology, 2020)
Macrophage plasticity is a process that allows macrophages to switch between two opposing phenotypes based on differential stimuli. Interferon gamma (IFNγ)-primed macrophages stimulated with lipopolysaccharide (LPS) (M(IFNγ +LPS)) produce high levels of proinflammatory cytokines such as IL-12, TNFα and IL-6 and low levels of the anti-inflammatory cytokine IL-10, while those stimulated with LPS in the presence of the immune complex (IC) (M(IFNγ +LPS+IC)) produce high levels of IL-10 and low levels of IL-12. In this study, we investigated the plasticity between M(IFNγ +LPS) and M(IFNγ +LPS+IC) in vitro and compared one of the active histone marks (histone H3 lysine 4 trimethylation (H3K4me3)) between M(IFNγ +LPS) and M(IFNγ +LPS+IC) using murine bone marrow-derived macrophages. We found that in an in vitro system, macrophages exhibited functional plasticity from M(LPS) to M(IC) upon repolarization after two days of washout period while IFNγ priming before LPS stimulation prevented this repolarization. Phosphorylation of p38, SAPK/JNK and NF-kappaB p65 in M(LPS+IC) repolarized from M(LPS) was similar to that in M(LPS+IC) polarized from resting macrophages. To obtain the epigenetic profiles of M(IFNγ +LPS) and M(IFNγ+LPS+IC), the global enrichment of H3K4me3 was evaluated. M(LPS) and M(IFNγ +LPS+IC) displayed marked differences in genome-wide enrichment of H3K4me3. M(IFNγ +LPS+IC) showed increased global enrichment of H3K4me3, whereas M(IFNγ +LPS) showed decreased enrichment when compared to unstimulated macrophages. Furthermore, M(IFNγ +LPS+IC) exhibited high levels of H3K4me3 enrichment in all cis-regulatory elements. At the individual gene level, the results showed increased H3K4me3 enrichment in the promoters of known genes associated with M(IFNγ +LPS+IC), including Il10, Cxcl1, Csf3 and Il33, when compared with those of M(IFNγ +LPS). Finally, we investigated the impact of M(IFNγ+LPS+IC) on the systemic immune response by adoptive transfer of M(IFNγ+LPS+IC) in an LPS-induced endotoxemia model. The cytokine profile revealed that mice with adoptively transferred M(IFNγ+LPS+IC) had acutely reduced serum levels of the inflammatory cytokines IL-1β and IL-p12p70. This study highlights the importance of epigenetics in regulating macrophage activation and the functions of M(IFNγ +LPS+IC) that may influence macrophage plasticity and the potential therapeutic use of macrophage transfer in vivo.